Closing address: Artistic Research in Africa - rethinking the "avant-garde" - Deribew, Berhanu Ashagrie (Arts Research Africa (ARA), 2020)
In order to implement artistic research in Africa need to recognize the different contexts - cultural, political and institutional – on our continent; and that artistic research is a subject not yet full clear in its function. The colonial model of the university has had the effect of “epistemicide” on indigenous knowledge. This aggravated by Western refusal to recognize traditions understand nature as Mother Earth with her own rights. Argues for a “rearguard” approach to art activism to learn from sources of embodied knowledge in communities.
Arts Research Africa Conference Proceeding 2020
Keywords: Artistic research; Arts research; Decolonisation; Arts pedagogy